2009
DOI: 10.1021/np8007396
|View full text |Cite
|
Sign up to set email alerts
|

Oleanane-Type Isomeric Triterpenoids from Barringtonia racemosa

Abstract: Two new isomeric acylated oleanane-type triterpenoids along with three known compounds were isolated from the MeOH extract of the dried fruits of Barringtonia racemosa. On the basis of spectroscopic methods, with special emphasis on 1D and 2D NMR techniques as well as chemical methods, the structures were characterized as racemosol A (1) [22alpha-acetoxy-3beta,15alpha,16alpha,21beta-tetrahydroxy-28-(2-methylbutyryl)olean-12-ene] and isoracemosol A (2) [21beta-acetoxy-3beta,15alpha,16alpha,28-tetrahydroxy-22alp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(16 citation statements)
references
References 19 publications
(16 reference statements)
1
15
0
Order By: Relevance
“…Furthermore, ROESY cross peaks at δ H 0.74 (3 H, s, H 3 ‐29)/5.48 (1H, d J = 9.3 Hz, H‐21) and 0.88 (3 H, s, H 3 ‐30)/4.03 (1H, H‐22) revealed the β ‐axial orientation of the H‐22, and the multiplicity as a doublet and the coupling constant of 9.3 Hz suggested an α ‐axial orientation of H‐21. This extensive 2D NMR analysis confirmed the identification of the aglycone of compound 2 as the already known sapogenol called R1‐barrigenol (olean‐12‐ene‐3 β ,15 α ,16 α ,21 β ,22 α ,28‐hexol), which is esterified at C‐21 by an acetyl function. In the 1 H NMR spectrum of compound 2 , signals of five anomeric protons were shown at δ H 5.06 (br s), 4.81 (d, J = 6.0 Hz), 4.72 (d, J = 7.3 Hz), 4.28 (d, J = 6.9 Hz) and 4.14 (d, J = 5.7 Hz), which correlated in the HSQC spectrum with five carbons at δ C 106.8, 101.9, 101.4, 103.6 and 104.6, respectively, indicating the presence of five sugar moieties.…”
Section: Resultssupporting
confidence: 63%
“…Furthermore, ROESY cross peaks at δ H 0.74 (3 H, s, H 3 ‐29)/5.48 (1H, d J = 9.3 Hz, H‐21) and 0.88 (3 H, s, H 3 ‐30)/4.03 (1H, H‐22) revealed the β ‐axial orientation of the H‐22, and the multiplicity as a doublet and the coupling constant of 9.3 Hz suggested an α ‐axial orientation of H‐21. This extensive 2D NMR analysis confirmed the identification of the aglycone of compound 2 as the already known sapogenol called R1‐barrigenol (olean‐12‐ene‐3 β ,15 α ,16 α ,21 β ,22 α ,28‐hexol), which is esterified at C‐21 by an acetyl function. In the 1 H NMR spectrum of compound 2 , signals of five anomeric protons were shown at δ H 5.06 (br s), 4.81 (d, J = 6.0 Hz), 4.72 (d, J = 7.3 Hz), 4.28 (d, J = 6.9 Hz) and 4.14 (d, J = 5.7 Hz), which correlated in the HSQC spectrum with five carbons at δ C 106.8, 101.9, 101.4, 103.6 and 104.6, respectively, indicating the presence of five sugar moieties.…”
Section: Resultssupporting
confidence: 63%
“…The hexane, ethanol, methanol extracts of seeds of B. racemosa reported to possess α-glucosidase and α-amylase inhibition activities (Gowri et al 2007). Gowri et al (2009) also reported the presence of pentacyclic triterpenoid bartogenic acid in the methanol extracts of this plant responsible for its antidiabetic activity.…”
Section: B Racemosamentioning
confidence: 91%
“…Several diterpenoids and triterpenoids have been identified in B. racemosa extract and a pentacyclic triterpenoid, bartogenic acid, is the major active component [138, 139]. The hexane, ethanol and methanol extracts as well as the pure compound of bartogenic acid inhibited intestinal α -glucosidase activity at concentrations ranging from 0.02–0.2  μ g/mL in an in vitro enzymatic study.…”
Section: Commonly Used Tcm/tim For T2dmmentioning
confidence: 99%